BNT162b vaccines are immunogenic and protect non-human primates against SARS-CoV-2 - Vogel, Annette B; Kanevsky, Isis; Ye Che; Swanson, Kena A; Muik, Alexander; Vormehr, Mathias; Kranz, Lena M; Walzer, Kerstin C; Hein, Stephanie; Güler, Alptekin; Loschko, Jakob; Maddur, Mohan S; et al. (bioRxiv, 2020)
Abstract A safe and effective vaccine against COVID-19 is urgently needed in quantities sufficient to immunise large populations. We report the preclinical development of two BNT162b vaccine candidates, which contain lipid-nanoparticle (LNP) formulated nucleoside-modified mRNA encoding SARS-CoV-2 spike glycoprotein-derived immunogens. BNT162b1 encodes a soluble, secreted, trimerised receptor-binding domain (RBD-foldon). BNT162b2 encodes the full-length transmembrane spike glycoprotein, locked in its prefusion conformation (P2 S). The flexibly tethered RBDs of the RBD-foldon bind ACE2 with high avidity. Approximately 20% of the P 2S trimers are in the two-RBD ‘down,’ one-RBD ‘up’ state. In mice, one intramuscular dose of either candidate elicits a dose-dependent antibody response with high virus-entry inhibition titres and strong TH1 CD4+ and IFNγ+ CD8+ T-cell responses. Prime/boost vaccination of rhesus macaques with BNT162b candidates elicits SARS-CoV-2 neutralising geometric mean titres 8.2 to 18.2 times that of a SARS-CoV-2 convalescent human serum panel. The vaccine candidates protect macaques from SARS-CoV-2 challenge, with BNT162b2 protecting the lower respiratory tract from the presence of viral RNA and with no evidence of disease enhancement. Both candidates are being evaluated in phase 1 trials in Germany and the United States. BNT162b2 is being evaluated in an ongoing global, pivotal Phase 2/3 trial (NCT04380701, NCT04368728). Competing Interest Statement U.S. and O.T. are management board members and employees at BioNTech SE (Mainz, Germany); K.C.W., B.G.L., D.S., B.J., T.H., T.K. and C.R. are employees at BioNTech SE; A.B.V., A.M., M.V., L.M.K., S.H., A.G., T.Z., F.B., A.P., D.E., S.C.D., S.F., S.E., F.B., B.S., A.W., Y.F., H.J., S.A.K., S.S., A.P.H., P.A., J.S., A.A.H.S., C.K., R.d.l.C.G.G., L.F. and A.N.K. are employees at BioNTech RNA Pharmaceuticals GmbH (Mainz, Germany); A.B.V., A.M., K.C.W., A.G., S.F., A.N.K and U.S. are inventors on patents and patent applications related to RNA technology and COVID-19 vaccine; A.B.V., A.M., M.V., L.M.K., K.C.W., S.H., B.G.L., A.P., D.E., S.C.D., S.F., S.E., D.S., B.J., B.S., A.P.H., P.A. J.S., A.A.H.S., T.H., L.F., C.K., T.K., C.R., A.N.K., O.T. and U.S. have securities from BioNTech SE; I.K., Y.C., K.A.S. J.A.L. M.S.M., K.T., A,O.-S., J.A.F., M.C.G., S.H., J.A.L., E.H.M., N.L.N., P.V.S., C.Y.T., D.P., W.V.K., J.O., R.S.S., S,C., T.C., I.L.S., M.W.P., G.S., and P.R.D., K.U.J. are employees of Pfizer and may hold stock options; C.F.-G. and P.-Y.S. received compensation from Pfizer to perform neutralisation assays; M.R.G. received compensation from Pfizer to read and interpret radiographs and CT scans. J.C., S.H.-U, K.B., R.C., Jr., K.J.A. O.G., and D.K., are employees of Southwest National Primate Research Center, which received compensation from Pfizer to conduct the animal challenge work; M.G. is an employee of Texas Biomedical Research Institute, which received compensation from Pfizer to conduct the RT-qPCR viral load quantification; no other relationships or activities that could appear to have influenced the submitted work.